2006
DOI: 10.1007/s10552-005-0453-9
|View full text |Cite
|
Sign up to set email alerts
|

Frequent Tanning Bed Use, Weight Concerns, and Other Health Risk Behaviors in Adolescent Females (United States)

Abstract: Frequent tanning bed use among adolescent females is associated with a range of health risk behaviors. This effect may be mediated by peer influence and a desire to look like other females in the media. Multi-pronged approaches, particularly those that target attitudes of young females, are needed to combat increased use of tanning beds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
94
4
4

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(107 citation statements)
references
References 45 publications
5
94
4
4
Order By: Relevance
“…However, efforts should be made to intensify current sun-protection programs while devising new and creative messages for children of this age, especially because the use of tanning beds, particularly for girls, begins at age 14. 21 A recent review of sun behavior counseling in children highlights the difficulties of changing these behaviors, but demonstrates that it is possible to decrease midday sun exposure and increase sunscreen use via counseling in the primary care setting. 22 With more than 80% of children in 2004 and 2007 reporting that they got a tan the previous summer and tan-promoting attitudes and practices increasing substantially from ages 11 to 14, new approaches must be taken to discourage tan-promoting attitudes that drive the desire for tan seeking from natural and artificial sources of UVR.…”
Section: Discussionmentioning
confidence: 99%
“…However, efforts should be made to intensify current sun-protection programs while devising new and creative messages for children of this age, especially because the use of tanning beds, particularly for girls, begins at age 14. 21 A recent review of sun behavior counseling in children highlights the difficulties of changing these behaviors, but demonstrates that it is possible to decrease midday sun exposure and increase sunscreen use via counseling in the primary care setting. 22 With more than 80% of children in 2004 and 2007 reporting that they got a tan the previous summer and tan-promoting attitudes and practices increasing substantially from ages 11 to 14, new approaches must be taken to discourage tan-promoting attitudes that drive the desire for tan seeking from natural and artificial sources of UVR.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to age and gender differences, adolescents with a more positive attitude toward tanning or tanned skin are more likely to use indoor tanning devices. [30][31][32][33][34][35][36][37][38][39] Perceived social norms regarding tanning and tanned skin (e.g., reporting that one's friends are tan or use indoor tanning devices) are also associated with indoor tanning among adolescents. 30,32,35,36,38 Indoor tanning is associated with other risky behaviors as well, such as alcohol, tobacco, and recreational drug use; poor sun protection behaviors; and unhealthy eating behaviors (such as dieting frequently to lose weight or using laxatives and vomiting to control weight).…”
Section: Correlates Of Indoor Tanningmentioning
confidence: 99%
“…[30][31][32][33][34][35][36][37][38][39] Perceived social norms regarding tanning and tanned skin (e.g., reporting that one's friends are tan or use indoor tanning devices) are also associated with indoor tanning among adolescents. 30,32,35,36,38 Indoor tanning is associated with other risky behaviors as well, such as alcohol, tobacco, and recreational drug use; poor sun protection behaviors; and unhealthy eating behaviors (such as dieting frequently to lose weight or using laxatives and vomiting to control weight). 32,34,38,39 One large study 39 found adolescents who had a college-educated mother were less likely to tan, and female adolescents who participated in physical activity were less likely to tan than peers who did not.…”
Section: Correlates Of Indoor Tanningmentioning
confidence: 99%
See 1 more Smart Citation
“…smoking, alcohol or caffeine consumption, physical activity, medications) known to affect bone or vitamin D status between the tanning and non-tanning groups. So while it has been reported that women who tan regularly also engage in more high risk behaviors than non-tanners, 41 the present study was designed to control or account for these behaviors through well-defi ned subject inclusion/exclusion criteria and the collection of pertinent questionnaire data for analysis. We are reasonably confident, therefore that our results may be extended to the general population of healthy women older than 25 years.…”
Section: Discussionmentioning
confidence: 99%